2009
DOI: 10.1016/j.ajhg.2009.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in BMP4 Are Associated with Subepithelial, Microform, and Overt Cleft Lip

Abstract: Cleft lip with or without cleft palate (CL/P) is a complex trait with evidence that the clinical spectrum includes both microform and subepithelial lip defects. We identified missense and nonsense mutations in the BMP4 gene in 1 of 30 cases of microform clefts, 2 of 87 cases with subepithelial defects in the orbicularis oris muscle (OOM), 5 of 968 cases of overt CL/P, and 0 of 529 controls. These results provide confirmation that microforms and subepithelial OOM defects are part of the spectrum of CL/P and sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
174
5
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 184 publications
(190 citation statements)
references
References 32 publications
9
174
5
2
Order By: Relevance
“…Normal variation at or near the time of fusion underestimates potential variation, as evidenced by the large number of genes known to contribute to primary cleft incidence and severity in humans (Dixon et al, 2011), many of which modulate the growth of prominences (Suzuki et al, 2009;Suazo et al, 2011). We targeted SHH signaling because of its known role in controlling mesenchymal growth zones,…”
Section: Resultsmentioning
confidence: 99%
“…Normal variation at or near the time of fusion underestimates potential variation, as evidenced by the large number of genes known to contribute to primary cleft incidence and severity in humans (Dixon et al, 2011), many of which modulate the growth of prominences (Suzuki et al, 2009;Suazo et al, 2011). We targeted SHH signaling because of its known role in controlling mesenchymal growth zones,…”
Section: Resultsmentioning
confidence: 99%
“…The nucleotide variant rs227731 is located 100kb centromeric of the NOG gene. NOG acts as antagonist of members of the TGF-b superfamily, which have been implicated in orofacial clefting 35 . Recently, Leslie et al 36 identified a common causative variant rs227727 near the NOG gene, which leads to disruption of its enhancer activity.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in components of the FGF and BMP signaling pathways have been shown to result in severe facial defects including cleft lip and cleft palate in humans and mice (Trumpp et al, 1999;Trokovic et al, 2003;Liu et al, 2005;Riley et al, 2007;Suzuki et al, 2009). Tbx22 is induced by FGF and inhibited by BMP signaling, raising the question, which roles of these pathways it may mediate.…”
Section: Functions Of Tbx22 Downstream Of Fgf and Bmp Signaling In Dementioning
confidence: 99%